Effects of feedback specificity on acquisition of trial‐based functional analysis skills. (19th May 2021) - Falligant, John M.; Pence, Sacha T.; Nuhu, Nadratu N.; Bedell, Sarah; Luna, Odessa
Abstract: Individuals responsible for training educational and support staff in schools and agencies may lack experience in evidence‐based training techniques. In particular, staff may have difficulty providing effective performance feedback, which is a critical component of many training models. Though many dimensions of feedback (e.g., accuracy, timing, consistency) may influence the effectiveness of feedback delivery, the impact of feedback specificity on performance is unknown. Accordingly, the purpose of the current study was to evaluate the effectiveness of feedback specificity (vague vs. specific) on acquisition of trial‐based functional analysis skills with eight graduate students studying applied behavior analysis. Overall, specific feedback was associated with improved skill acquisition for all trainees, whereas vague feedback actually decreased performance, relative to baseline, for three trainees. Implications for staff training practices and future areas of research will be discussed.